Mutations in Desmin's carboxy-terminal “Tail” domain severely modify filament and network mechanics - Bär, Harald; Schopferer, Michael; Sharma, Sarika; Hochstein, Bernhard; Mücke, Norbert; Herrmann, Harald; Willenbacher, Norbert (Journal of molecular biology, 2010)
Inherited mutations in the gene coding for the intermediate filament protein desmin have been demonstrated to cause severe skeletal and cardiac myopathies. Unexpectedly, some of the mutated desmins, in particular those carrying single amino acid alterations in the non-α-helical carboxy-terminal domain (“tail”), have been demonstrated to form apparently normal filaments both in vitro and in transfected cells. Thus, it is not clear if filament properties are affected by these mutations at all. For this reason, we performed oscillatory shear experiments with six different desmin “tail” mutants in order to characterize the mesh size of filament networks and their strain stiffening properties. Moreover, we have carried out high-frequency oscillatory squeeze flow measurements to determine the bending stiffness of the respective filaments, characterized by the persistence length lp. Interestingly, mesh size was not altered for the mutant filament networks, except for the mutant DesR454W, which apparently did not form proper filament networks. Also, the values for bending stiffness were in the same range for both the “tail” mutants (lp=1.0-2.0 μm) and the wild-type desmin (lp=1.1±0.5 μm). However, most investigated desmin mutants exhibited a distinct reduction in strain stiffening compared to wild-type desmin and promoted nonaffine network deformation. Therefore, we conclude that the mutated amino acids affect intrafilamentous architecture and colloidal interactions along the filament in such a way that the response to applied strain is significantly altered. In order to explore the importance of the “tail” domain as such for filament network properties, we employed a “tail”-truncated desmin. Under standard conditions, it formed extended regular filaments, but failed to generate strain stiffening. Hence, these data strongly indicate that the “tail” domain is responsible for attractive filament-filament interactions. Moreover, these types of interactions may also be relevant to the network properties of the desmin cytoskeleton in patient muscle.
Gesehen am 29.11.2022